ORANGE JUICER - Ashraf Adnan Sheikh Ali; Tareq Jamel Msameh (My University, 2010)
The main idea of our project is to make a system which responsible for all the new technology in our modern life and added a new idea with new technology to our modern life, in which it can make the topic what we want to talk about easier. Our project is an orange juicer which can by itself and its design separate the orange pieces and cut them after that squeeze them before it finally through them out, all of that by a special design will be discussed step by step in our project and thats is the main idea of our project. The advantages of our project is to make the operation of juicing oranges by separate, cut, squeeze and through out the juiced pieces more easy, and depend on one bottom, addition it can squeeze more than twenty pieces of orange in one minute, and it can be used in homes, hotels and the markets which makes several juice. During our project, the project itself will be passed through three stages, soft ware design by using AUTOCAD and MECHANICAL DESKTOP programs, wooden and cartoon model and finally the final model made by steel and plastic apparatus. Our project has many topics to be discussed that we have been studied during bachelor of mechanical engineering in several courses such as mechanical engineering design, machinery, statics, dynamics, and mechanical vibration. Finally, it will be a trial do it with full of effort and we hope to be a good idea and a good graduation project for all whom helped us to reach this stage of study and for our country, our university, mechanical engineering department and for all people.

The main idea of our project is to make a system which responsible for all the new technology in our modern life and added a new idea with new technology to our modern life, in which it can make the topic what we want to talk about easier. Our project is an orange juicer which can by itself and its design separate the orange pieces and cut them after that squeeze them before it finally through them out, all of that by a special design will be discussed step by step in our project and thats is the main idea of our project. The advantages of our project is to make the operation of juicing oranges by separate, cut, squeeze and through out the juiced pieces more easy, and depend on one bottom, addition it can squeeze more than twenty pieces of orange in one minute, and it can be used in homes, hotels and the markets which makes several juice. During our project, the project itself will be passed through three stages, soft ware design by using AUTOCAD and MECHANICAL DESKTOP programs, wooden and cartoon model and finally the final model made by steel and plastic apparatus. Our project has many topics to be discussed that we have been studied during bachelor of mechanical engineering in several courses such as mechanical engineering design, machinery, statics, dynamics, and mechanical vibration. Finally, it will be a trial do it with full of effort and we hope to be a good idea and a good graduation project for all whom helped us to reach this stage of study and for our country, our university, mechanical engineering department and for all people.
ORANGE JUICER